Heat-conducting silica gel as well as preparation method and application thereof
By synergistically modifying graphene and alumina powder, and utilizing π-π interactions and carboxyl bridging, an alumina-graphene composite filler is formed, which solves the problem of low thermal conductivity of silicone rubber and realizes thermally conductive silicone with high thermal conductivity and good mechanical properties.
Patent Information
- Application Number
- CN202610185013.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-09
- Publication Date
- 2026-05-26
AI Technical Summary
Silicone rubber has low thermal conductivity, and alumina particles tend to agglomerate, affecting the material's thermal conductivity and heat dissipation performance. Graphene and alumina are also difficult to bond tightly together.
Glutamic acid-based perylene tetracarboxylic acid diimide was used to synergistically modify graphene and alumina powder. Through π-π interactions and carboxyl bridging, an alumina-graphene composite filler was formed, which uniformly filled the gaps between large alumina particles to form a continuous thermal conduction path.
It significantly improves the thermal conductivity and heat dissipation performance of silicone while maintaining good mechanical properties and structural stability, making it suitable for high-temperature environments.
Smart Images

Figure SMS_4
Abstract
Description
Technical Field
[0001] This invention relates to the field of silicone rubber technology, specifically to a thermally conductive silicone rubber, its preparation method, and its application. Background Technology
[0002] Thermally conductive materials possess high thermal conductivity, enabling efficient heat transfer and dissipation from high-temperature regions to low-temperature regions during heat transfer, achieving excellent heat dissipation effects. They are widely used in electronics, new energy vehicles, aerospace, and other fields. Adding inorganic thermally conductive fillers to organic polymers can yield composite materials that combine high thermal conductivity, high flexibility, and ease of processing and molding.
[0003] Silicone rubber is highly flexible, has strong high-temperature resistance, and good adhesion, making it important in thermally conductive sealants and other applications. Typically, thermally conductive fillers such as alumina, boron nitride, and graphene are added to the silicone rubber matrix. Alumina is inexpensive, readily available, has high thermal conductivity, and is easy to surface modify, making it an ideal thermally conductive filler. However, alumina particles tend to agglomerate, and the gaps between large particles prevent the formation of good thermal conductive pathways, affecting the material's thermal conductivity and heat dissipation performance. Graphene possesses a nano-size effect and exhibits excellent mechanical strength and thermal conductivity. This invention aims to use modified alumina and graphene as composite thermally conductive fillers to improve the thermal conductivity and mechanical properties of silicone rubber. Summary of the Invention
[0004] This invention solves the problem of low thermal conductivity of silicone rubber.
[0005] The technical solution of the present invention is: a thermally conductive silicone rubber, comprising methyl vinyl silicone rubber, hydroxyl silicone oil, vulcanizing agent, and alumina-graphene composite filler in a mass ratio of 100:(0.8-1.3):(0.7-1):(30-60).
[0006] The preparation method of thermally conductive silicone is as follows: (1) Graphene was added to an ethanol aqueous solution, ultrasonically dispersed, and then glutamic acid peryltetracarboxylic acid diimide was added for surface modification. Then alumina micro powder was added for secondary modification. After filtration, the mixture was washed with water and ethanol and dried to obtain alumina-graphene composite filler.
[0007] (2) Add methyl vinyl silicone rubber, hydroxyl silicone oil and alumina-graphene composite filler into a mixer and mix them evenly. Then add vulcanizing agent, mix and place in a flat vulcanizing machine for vulcanization to obtain thermally conductive silicone.
[0008] Preferably, the vulcanizing agent includes 2,5-dimethyl-2,5-di(tert-butylperoxide)hexane and dicumyl peroxide.
[0009] Preferably, the volume fraction of the ethanol aqueous solution is 25-40%.
[0010] Preferably, the mass ratio of graphene, glutamic acid perylenetetracarboxylic acid diimide, and alumina micro powder is (2-7):(1-4):100.
[0011] Preferably, the surface modification temperature is 20-30℃ and the time is 1-2h.
[0012] Preferably, the temperature for secondary modification is 20-70℃ and the time is 1-3h.
[0013] Preferably, vulcanization is carried out first at 155-170℃ and 5-8MPa pressure for 20-30 minutes, and then at 220-230℃ for 1-1.5 hours.
[0014] Preferably, the preparation method of glutamate-based perylenetetracarboxylic acid diimide is as follows: 3,4,9,10-perylenetetracarboxylic acid dianhydride and glutamic acid are added to N,N-dimethylformamide, and the mixture is stirred to react. The solution is then added to ethanol, stirred, filtered, and the precipitate is added to water. Hydrochloric acid is added dropwise to adjust the pH to 3-4. After filtration, the precipitate is dried to obtain glutamate-based perylenetetracarboxylic acid diimide. The reaction formula is: .
[0015] Preferably, the molar ratio of 3,4,9,10-perylenetetracarboxylic dianhydride to glutamic acid is 1:(2-2.1).
[0016] Preferably, the reaction is carried out at 110-130℃ for 9-14 hours.
[0017] Preferably, thermally conductive silicone is used in high thermal conductivity heat dissipation materials.
[0018] The beneficial technical effects of this invention are as follows: Glutamic acid-based perylene tetracarboxylic acid diimide is used to synergistically modify graphene and alumina powder. The perylene diimide ring has a rigid conjugated plane, which can form π-π interactions and accumulate with the graphene surface, achieving non-covalent modification of the graphene surface. Furthermore, glutamic acid-based perylene tetracarboxylic acid diimide contains four carboxyl groups, forming a stronger interaction with the alumina particle surface. This allows glutamic acid-based perylene tetracarboxylic acid diimide to act as a bridging agent, tightly binding graphene nanoparticles and alumina microparticles. The tiny graphene nanoparticles can uniformly and tightly fill the gaps between the large alumina particles, reducing the gaps and interface defects between them, thereby forming a continuous thermal conductive path and significantly improving the thermal conductivity and heat dissipation performance of the silicone.
[0019] In this invention, the non-covalently modified graphene and the surface-modified alumina have better dispersibility and improved compatibility with silicone rubber, enabling the silicone material to maintain good mechanical properties, with greater hardness and tear strength. Using high-temperature resistant vulcanized silicone rubber as the matrix of the thermally conductive material, the material can maintain good structural stability and thermal conductivity and heat dissipation performance under high-temperature conditions. Detailed Implementation
[0020] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0021] Example 1
[0022] (1) Add 30 mmol of 3,4,9,10-perylenetetracarboxylic acid dianhydride and 60 mmol of glutamic acid to 200 mL of N,N-dimethylformamide, heat to 120 °C, stir and react for 12 h, add the solution to ethanol, stir, filter and add the precipitate to water, add 10% hydrochloric acid to adjust the pH to 4, filter and dry the precipitate to obtain glutamic acid-based perylenetetracarboxylic acid diimide.
[0023] (2) Add 10g of graphene (particle size between 3-9nm, Nangong Jiuxin New Materials, the same below) to 4L of 30% ethanol aqueous solution. After ultrasonic dispersion, add 5g of glutamic acid perylene tetracarboxylic acid diimide. Stir and modify at 20℃ for 2h. Then add 500g of alumina micro powder (average particle size 5μm, Hangzhou Jiayou New Materials, the same below). Stir and modify at 40℃ for 1h. After filtration, wash with water and ethanol, and dry to obtain alumina-graphene composite filler.
[0024] (3) Add 1 kg of methyl vinyl silicone rubber (model Dow Corning RBG-0618, Guangzhou Shenkai Trading, the same below), 11 g of hydroxyl silicone oil (model Wacker WS62M, Guangzhou Shenkai Trading, the same below), and 300 g of alumina-graphene composite filler to a mixer and mix well. Then add 10 g of 2,5-dimethyl-2,5-di(tert-butylperoxide)hexane, mix and place in a flat vulcanizing machine. First, vulcanize at 160℃ and 8MPa pressure for 30 min, and then vulcanize at 220℃ for 1.5 h to obtain thermally conductive silicone.
[0025] Example 2
[0026] (1) Add 30 mmol of 3,4,9,10-perylenetetracarboxylic acid dianhydride and 63 mmol of glutamic acid to 300 mL of N,N-dimethylformamide, heat to 110 °C, stir and react for 14 h, add the solution to ethanol, stir and filter, add the precipitate to water, add 15% hydrochloric acid to adjust the pH to 3, filter and dry the precipitate to obtain glutamic acid-based perylenetetracarboxylic acid diimide.
[0027] (2) Add 20g of graphene to 5L of 40% ethanol aqueous solution, disperse by ultrasonication, add 12g of glutamic acid perylene tetracarboxylic acid diimide, stir and modify at 20℃ for 2h, then add 500g of alumina micro powder, stir and modify at 20℃ for 3h, filter, wash with water and ethanol, and dry to obtain alumina-graphene composite filler.
[0028] (3) Add 1 kg of methyl vinyl silicone rubber, 13 g of hydroxyl silicone oil and 450 g of alumina-graphene composite filler to a mixer and mix well. Then add 7 g of dicumyl peroxide and mix in a flat vulcanizing machine. First, vulcanize at 170°C and 5 MPa for 30 min, and then vulcanize at 230°C for 1 h to obtain thermally conductive silicone.
[0029] Example 3
[0030] (1) Add 30 mmol of 3,4,9,10-perylenetetracarboxylic acid dianhydride and 60 mmol of glutamic acid to 200 mL of N,N-dimethylformamide, heat to 130 °C, stir and react for 9 h, add the solution to ethanol, stir and filter, add the precipitate to water, add 15% hydrochloric acid to adjust the pH to 3, filter and dry the precipitate to obtain glutamic acid-based perylenetetracarboxylic acid diimide.
[0031] (2) Add 35g of graphene to 6L of 25% ethanol aqueous solution, disperse by ultrasonication, add 20g of glutamic acid perylene tetracarboxylic acid diimide, stir and modify at 30℃ for 1h, then add 500g of alumina micro powder, stir and modify at 70℃ for 2h, filter, wash with water and ethanol, and dry to obtain alumina-graphene composite filler.
[0032] (3) Add 1 kg of methyl vinyl silicone rubber, 8 g of hydroxyl silicone oil and 600 g of alumina-graphene composite filler to a mixer and mix well. Then add 9 g of 2,5-dimethyl-2,5-di(tert-butylperoxide)hexane, mix and place in a flat vulcanizing machine. First, vulcanize at 155℃ and 8 MPa for 20 min, and then vulcanize at 230℃ for 1 h to obtain thermally conductive silicone.
[0033] Comparative Example 1 (1) Add 10g of graphene to 4L of 30% ethanol aqueous solution, disperse by ultrasonication, stir at 20℃ for 2h, then add 500g of alumina micro powder, stir at 40℃ for 1h, filter, wash with water and ethanol, and dry to obtain alumina-graphene composite filler.
[0034] (2) Add 1 kg of methyl vinyl silicone rubber, 11 g of hydroxyl silicone oil, and 300 g of alumina-graphene composite filler to a mixer and mix well. Then add 10 g of 2,5-dimethyl-2,5-di(tert-butylperoxide)hexane, mix and place in a flat vulcanizing machine. First, vulcanize at 160°C and 8 MPa for 30 min, and then vulcanize at 220°C for 1.5 h to obtain thermally conductive silicone.
[0035] Comparative Example 2 (1) Add 30 mmol of 3,4,9,10-perylenetetracarboxylic dianhydride and 60 mmol of n-butylamine to 200 mL of N,N-dimethylformamide, heat to 120 °C, stir and reflux for 12 h, add the solution to water, stir and filter, wash the precipitate with water and petroleum ether to obtain butylaminoperylenetetracarboxylic acid diimide, with the structural formula: .
[0036] (2) Add 10g of graphene to 4L of 30% ethanol aqueous solution, disperse it by ultrasonication, add 5g of butylamine perylene tetracarboxylic acid diimide, stir and modify at 20℃ for 2h, then add 500g of alumina micro powder, stir and modify at 40℃ for 1h, filter, wash with water and ethanol, and dry to obtain alumina-graphene composite filler.
[0037] (3) Add 1 kg of methyl vinyl silicone rubber, 11 g of hydroxyl silicone oil and 300 g of alumina-graphene composite filler to a mixer and mix well. Then add 10 g of 2,5-dimethyl-2,5-di(tert-butylperoxide)hexane, mix and place in a flat vulcanizing machine. First, vulcanize at 160°C and 8 MPa for 30 min, and then vulcanize at 220°C for 1.5 h to obtain thermally conductive silicone.
[0038] Comparative Example 3 (1) Add 30 mmol of 3,4,9,10-perylenetetracarboxylic acid dianhydride and 60 mmol of glycine to 200 mL of N,N-dimethylformamide, heat to 120 °C, stir and react for 12 h, add the solution to ethanol, stir and filter, add the precipitate to water, add 10% hydrochloric acid to adjust the pH to 4, filter and dry the precipitate to obtain glycine-based perylenetetracarboxylic acid diimide.
[0039] .
[0040] (2) Add 10g of graphene to 4L of 30% ethanol aqueous solution, disperse by ultrasonication, add 5g of glycine-based perylenetetracarboxylic acid diimide, stir and modify at 20℃ for 2h, then add 500g of alumina micro powder, stir and modify at 40℃ for 1h, filter, wash with water and ethanol, and dry to obtain alumina-graphene composite filler.
[0041] (3) Add 1 kg of methyl vinyl silicone rubber, 11 g of hydroxyl silicone oil and 300 g of alumina-graphene composite filler to a mixer and mix well. Then add 10 g of 2,5-dimethyl-2,5-di(tert-butylperoxide)hexane, mix and place in a flat vulcanizing machine. First, vulcanize at 160°C and 8 MPa for 30 min, and then vulcanize at 220°C for 1.5 h to obtain thermally conductive silicone.
[0042] Comparative Example 4 (1) Add 10g of graphene to 4L of 30% ethanol aqueous solution, disperse by ultrasonication, add 5g of stearic acid, stir and modify at 20℃ for 2h, then add 500g of alumina micro powder, stir and modify at 40℃ for 1h, filter, wash with water and ethanol, and dry to obtain alumina-graphene composite filler.
[0043] (2) Add 1 kg of methyl vinyl silicone rubber, 11 g of hydroxyl silicone oil, and 300 g of alumina-graphene composite filler to a mixer and mix well. Then add 10 g of 2,5-dimethyl-2,5-di(tert-butylperoxide)hexane, mix and place in a flat vulcanizing machine. First, vulcanize at 160°C and 8 MPa for 30 min, and then vulcanize at 220°C for 1.5 h to obtain thermally conductive silicone.
[0044] The thermal conductivity of silicone is tested according to GB / T 11205-2009 standard. Hardness is tested according to GB / T 531.1-2008 standard. Tear strength is tested according to GB / T 529-2008 standard.
[0045] Table 1 Performance Tests of Silicone
[0046] Compared to Comparative Example 1, the glutamate-based perylenetetracarboxylic acid diimide in Example 1 contains a perylene diimide ring with a rigid conjugated plane, which can form π-π interactions and accumulate with the graphene surface, achieving non-covalent modification of the graphene surface. Furthermore, the glutamate-based perylenetetracarboxylic acid diimide contains four carboxyl groups, forming a stronger interaction with the alumina particle surface. This allows the glutamate-based perylenetetracarboxylic acid diimide to act as a bridging agent, tightly binding the graphene nanoparticles and alumina microparticles. The tiny graphene nanoparticles can uniformly and tightly fill the gaps between the large alumina particles, thus forming a continuous thermally conductive pathway, significantly improving the thermal conductivity and heat dissipation performance of the silicone. Moreover, the non-covalently modified graphene and surface-modified alumina exhibit better dispersibility and improved compatibility with silicone rubber, allowing the silicone material to maintain good mechanical properties, with higher hardness and tear strength. In Examples 2 and 3, by adding different amounts of alumina-graphene composite filler, silica gel also exhibits higher thermal conductivity and good mechanical strength.
[0047] The butylaminoperyltetracarboxylic acid diimide in Comparative Example 2 does not contain a carboxyl group, making it difficult to form an interaction with the alumina surface. It cannot act as a bridging agent and cannot tightly bind the graphene nanoparticles and alumina powder. Gaps will form between graphene and alumina, resulting in interface defects that affect the mechanical strength of the silicone. Consequently, the thermal conductivity, hardness, and tear strength of the silicone are all lower than those in Example 1.
[0048] Comparative Example 3 has a lower carboxyl content in glycine-based perylenetetracarboxylic acid diimide, resulting in a weaker interaction with the alumina surface and a lower bridging effect than Example 1. Consequently, the thermal conductivity, hardness, and tear strength of the silicone are all lower than those of Example 1.
[0049] The stearic acid in Comparative Example 4 does not contain a perylene diimide ring structure, making it difficult to form π-π interactions and non-covalent modifications with graphene. It is difficult to act as a bridging agent and cannot tightly bind graphene nanoparticles with alumina microparticles. The thermal conductivity, hardness, and tear strength of the silicone are all lower than those in Example 1.
[0050] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.
Claims
1. A thermally conductive silicone rubber, characterized in that, The thermally conductive silicone rubber comprises methyl vinyl silicone rubber, hydroxyl silicone oil, vulcanizing agent, and alumina-graphene composite filler in a mass ratio of 100:(0.8-1.3):(0.7-1):(30-60). The alumina-graphene composite filler is prepared by the following method: graphene is added to an ethanol aqueous solution, ultrasonically dispersed, and then glutamic acid-based perylenetetracarboxylic acid diimide is added for surface modification. Then, alumina micro powder is added for secondary modification, filtered, washed, and dried to obtain the alumina-graphene composite filler.
2. The thermally conductive silicone according to claim 1, characterized in that, The vulcanizing agent includes 2,5-dimethyl-2,5-di(tert-butylperoxide)hexane and dicumyl peroxide.
3. The thermally conductive silicone according to claim 1, characterized in that, The volume fraction of the ethanol-water solution is 25-40%.
4. The thermally conductive silicone according to claim 1, characterized in that, The mass ratio of graphene, glutamic acid perylene tetracarboxylic acid diimide, and alumina micro powder is (2-7):(1-4):
100.
5. The thermally conductive silicone according to claim 1, characterized in that, The surface modification is performed at a temperature of 20-30℃ for 1-2 hours.
6. The thermally conductive silicone according to claim 1, characterized in that, The secondary modification is performed at a temperature of 20-70℃ for 1-3 hours.
7. The thermally conductive silicone according to claim 4, characterized in that, The preparation method of the glutamate-based perylenetetracarboxylic acid diimide is as follows: 3,4,9,10-perylenetetracarboxylic acid dianhydride and glutamic acid are added to N,N-dimethylformamide in a molar ratio of 1:(2-2.1), heated to 110-130℃, and stirred for 9-14 hours. The solution is then added to ethanol, stirred and filtered, and the precipitate is added to water. Hydrochloric acid is added dropwise to adjust the pH to 3-4. After filtration, the precipitate is dried to obtain glutamate-based perylenetetracarboxylic acid diimide.
8. A method for preparing thermally conductive silicone as described in any one of claims 1-7, characterized in that, The preparation method is as follows: methyl vinyl silicone rubber, hydroxyl silicone oil, and alumina-graphene composite filler are added to a mixer and mixed evenly. Then, a vulcanizing agent is added, and the mixture is placed in a flat vulcanizing machine for vulcanization to obtain thermally conductive silicone.
9. The method for preparing thermally conductive silicone according to claim 8, characterized in that, The vulcanization process involves first performing the vulcanization at 155-170℃ and 5-8MPa pressure for 20-30 minutes, followed by a process at 220-230℃ for 1-1.5 hours.
10. The application of a thermally conductive silicone obtained by the preparation method as described in claim 9 in a high thermal conductivity heat dissipation material.
